CHARACTERISTICS OF SOIL TENSION AT DIFFERENT AGES OF ACACIA PLANTATION FOREST IN A LUONG SON HEADWATER OF HOA BINH, VIETNAM - Thi Kim Thanh, Do; Xuan Dung, Bui; Gomi, Takashi (Journal of Forestry Science and Technology, 2020)
To determine the characteristics of soil tension at different ages of Acacia plantation forest, plots were established at different vegetation cover conditions such as bare land after cutting, 1 years-old Acacia trees, 3-years-old Acacia trees, and 5-years-old Acacia plantation in Truong Son Commune, Luong Son district, Hoa Binh province. Soil tension was measured by tensionmeter at 36 points of 3 depths such as 30 cm, 60 cm, 90 cm from 10th to 30th August 2020. Affecting factors on soil tension were also determined, including forest structure, soil physical characteristics of Acacia plantation. The main findings included: (1) Canopy cover, litter and understory vegetation cover tend to be increased following to age of Acacia plantation while tree density decrease. Soil moisture recorded an increase ranged from 19.1% to 22% and decrease with increasing of ages. Soil texture of silt higher than clay and sand; (2) Soil tension tend to be decreased from 36.2 kPa in 1-years-old to 9.17 kPa in 5-years-old and increase when the soil depth become deeper. Soil tension has a strong relationship with vegetation factors, soil moisture, sand, clay and weak relationship with porosity, silt. This results suggest decreasing of available water capacity of soil following to ages and lowest at bare soil after cutting, 1 year-old Acacia. Thus, proposing some solutions to control available water capacity of soil at different ages of Acacia plantation forest in headwater is necessary.